Receptor-like kinase OsSIK1 improves drought and salt stress tolerance in rice (Oryza sativa) plants - Ouyang, Shou-Qiang; Liu, Yun-Feng; Liu, Peng; Lei, Gang; He, Si-Jie; Ma, Biao; Zhang, Wan-Ke; Zhang, Jin-Song; Chen, Shou-Yi (The Plant journal : for cell and molecular biology, 2010)
Receptor-like kinases (RLKs) play essential roles in plant growth, development and responses to environmental stresses. A putative RLK gene, OsSIK1, with extracellular leucine-rich repeats was cloned and characterized in rice (Oryza sativa). OsSIK1 exhibits kinase activity in the presence of Mn²⁺, and the OsSIK1 kinase domain has the ability to autophosphorylate and phosphorylate myelin basic protein (MBP). OsSIK1 promoter-GUS analysis revealed that OsSIK1 is expressed mainly in the stem and spikelet in rice. The expression of OsSIK1 is mainly induced by salt, drought and H₂O₂ treatments. Transgenic rice plants with overexpression of OsSIK1 show higher tolerance to salt and drought stresses than control plants. On the contrary, the knock-out mutants sik1-1 and sik1-2, as well as RNA interference (RNAi) plants, are sensitive to drought and salt stresses. The activities of peroxidase, superoxide dismutase and catalase are enhanced significantly in OsSIK1-overexpressing plants. Also, the accumulation of H₂O₂ in leaves of OsSIK1-overexpressing plants is much less than that of the mutants, RNAi plants and control plants, as measured by 3,3′-diamino benzidine (DAB) staining. We also show that OsSIK1 affects stomatal density in the abaxial and adaxial leaf epidermis of rice. These results indicate that OsSIK1 plays important roles in salt and drought stress tolerance in rice, through the activation of the antioxidative system.